Development of Board Game Media on Air Theme for Children Aged 5-6 Years - Nenny Mahyuddin; Rani Sofiya; Andi Agusniati; Yuliani Nurani; Dony Novaliendry; Elida (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Board games are educational tools consisting of a board with boxes drawn on it. In this game, there are several rules that must be followed, which involve social interaction between children during playtime. This study aims to develop a board game on the theme of air to support children’s growth and development as well as enhance their knowledge related to the topic. Moreover, this R&D study employed 4D development with data analysis techniques for validation, practicality, and effectiveness. The data were collected through interviews and expert validation of the product. Moreover, this study has reached the fourth stage, which is dissemination. The population of this study consisted of 65 children aged 5–6 years at Aisyiyah Sicincin Kindergarten, Padang Pariaman Regency. Based on the results, it was found that board game media are effective in promoting children’s growth and development in terms of cognitive, linguistic, and motor skills.